Probabilistic Fusion of Stereo with Color and Contrast for Bi-Layer Segmentation - Kolmogorov, Vladimir; Criminisi, Antonio; Blake, Andrew; Cross, Geoffrey; Rother, Carsten (International Journal of Computer Vision, 2008)
na